If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7x + -7 = 63 Reorder the terms: -7 + -7x = 63 Solving -7 + -7x = 63 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + -7x = 63 + 7 Combine like terms: -7 + 7 = 0 0 + -7x = 63 + 7 -7x = 63 + 7 Combine like terms: 63 + 7 = 70 -7x = 70 Divide each side by '-7'. x = -10 Simplifying x = -10
| 5a+10b=30 | | 0.5p^2=4p-8 | | -2a^2+6a=5 | | 9m-16=m | | 5*8+9+4=53 | | 0.5/2.5 | | 145000000/1.16= | | -x^2-15x+4=0 | | 5*(8+9)+4=89 | | 2x-25=55 | | 504*.14= | | 5b+2p=144 | | (15n^2-5n+45)/5 | | 6y+16=-4y-4 | | X^2=y^2+9 | | y=5x^2-15x | | 3t^2+7t+4=0 | | 18+x=21 | | s^2-4s=32 | | 7a+5b=19.5 | | 9m=27 | | a^2+8=3k | | 4x+9y=17 | | 16-4x^2=0 | | 43x-23=65 | | 43x-23= | | 43-23= | | 43-23+54= | | f(x)=x^2-18x+65 | | 20x-34=55 | | 105+4x=203 | | 2=-1+x/-16 |